Adapting to the new normal: Remote teaching challenges among educators in higher education - Maura Gina D. Ramoso; Ruth Ortega-Dela Cruz (S&Co Publishing, 2024)
The Covid-19 pandemic has led Higher Education Institutions (HEIs) in the Philippines to replace on-campus learning with remote teaching. This study employed a quantitative approach using online surveys to explore the challenges of 39 faculty members on remote teaching implementation in a State College in the Philippines. Findings revealed that problems related to actual delivery of instruction, access to technologies or gadgets needed for teaching, internet connectivity, additional non-teaching tasks assignment were some of the challenges faced by educators. Furthermore, the study revealed a significant relationship between some educators’ demographics, and their perceived challenges of remote teaching. The results of Kendall's W revealed congruence in the perceptions of the most challenging aspects of remote teaching among educators in higher education. This pandemic is not the first, nor will it be the last, to impact the higher education system. Thus, there is a need to find ways on how educators could be able to adjust with the basic requirements for successful implementation of remote teaching. All stakeholders are enjoined to develop strategies that can be implemented in the short-term as well as long-term. A dialogue between and among members of the academic community is therefore critical in making informed policy to adapt to the new normal in higher education.